Homojunction of Oxygen and Titanium Vacancies and its Interfacial n–p Effect - Wu, Si‐Ming; Liu, Xiao‐Long; Lian, Xi‐Liang; Tian, Ge; Janiak, Christoph; Zhang, Yue‐Xing; Lu, Yi; Yu, Hao‐Zheng; Hu, Jie; Wei, Hao; Zhao, Heng; Chang, Gang‐Gang; et al. (Advanced materials (Weinheim), 2018)
The homojunction of oxygen/metal vacancies and its interfacial n–p effect on the physiochemical properties are rarely reported. Interfacial n–p homojunctions of TiO2 are fabricated by directly decorating interfacial p‐type titanium‐defected TiO2 around n‐type oxygen‐defected TiO2 nanocrystals in amorphous–anatase homogeneous nanostructures. Experimental measurements and theoretical calculations on the cell lattice parameters show that the homojunction of oxygen and titanium vacancies changes the charge density of TiO2; a strong EPR signal caused by oxygen vacancies and an unreported strong titanium vacancies signal of 2D 1H TQ‐SQ MAS NMR are present. Amorphous–anatase TiO2 shows significant performance regarding the photogeneration current, photocatalysis, and energy storage, owing to interfacial n‐type to p‐type conductivity with high charge mobility and less structural confinement of amorphous clusters. A new “homojunction of oxygen and titanium vacancies” concept, characteristics, and mechanism are proposed at an atomic‐/nanoscale to clarify the generation of oxygen vacancies and titanium vacancies as well as the interface electron transfer. The homojunction of oxygen and titanium vacancies developed in the amorphous–anatase interface of nanostructured TiO2 results in a unique n–p electronic transmission, which is mostly preferred to the mobility of electronic charge carriers. It also contributes to significant performance regarding photogeneration current, photocatalysis, and energy storage.